PENGARUH KOMPENSASI DAN HUBUNGAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN (STUDI PADA RUMAH MAKAN SOTO BANGKONG, JL. BRIGJEN KATAMSO 1, SEMARANG) - Albela Mayarani Puspita; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2018)
The problem of this research is the increasing of customer complain on service shown by the employee and the result of observation indicate the decrease of work motivation. So that the research problem is how to increase work motivation at RM Soto Bangkong, Semarang. The work motivation at RM Soto Bangkong, Semarang is allegedly influenced by compensation and work relations. This research was conducted to find out the compensation and work relationships influence the work motivation of employees of RM Soto Bangkong, Semarang. In this study using census sampling techniques so that 53 employees of RM Soto Bangkong, Semarang can be taken. The data analysis used is regression. The results showed that compensation has a positive and significant effect on employee motivation RM Soto Bangkong, Semarang, working relationship has a positive and significant influence on employee work motivation RM Soto Bangkong, Semarang. The results also indicate that there is a positive and significant influence between compensation and working relationships together towards employee motivation RM Soto Bangkong, Semarang.